2010
DOI: 10.1016/j.ultsonch.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hydrogels via ultrasonic polymerization

Abstract: Several acrylic hydrogels were prepared via ultrasonic polymerization of water soluble monomers and macromonomers. Ultrasound was used to create initiating radicals in viscous aqueous monomer solutions using the additives glycerol, sorbitol or glucose in an open system at 37 degrees C. The water soluble additives were essential for the hydrogel production, glycerol being the most effective. Hydrogels were prepared from the monomers 2-hydroxyethyl methacrylate, poly(ethylene glycol) dimethacrylate, dextran meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The polymerization does not require the use of chemical initiators, although water-soluble additives (sorbitol, glucose or glycerol, especially the latter) are essential for success. 52 This can be attributed to various effects, notably an increase in the population of secondary alkyl radicals which are more stable than hydroxyl radicals. Furthermore, glycerol leads to more viscous solutions, thereby reducing the polymer solubility and hence avoiding depolymerization side reactions.…”
Section: Ultrasound Effects On Polymer Formationmentioning
confidence: 99%
“…The polymerization does not require the use of chemical initiators, although water-soluble additives (sorbitol, glucose or glycerol, especially the latter) are essential for success. 52 This can be attributed to various effects, notably an increase in the population of secondary alkyl radicals which are more stable than hydroxyl radicals. Furthermore, glycerol leads to more viscous solutions, thereby reducing the polymer solubility and hence avoiding depolymerization side reactions.…”
Section: Ultrasound Effects On Polymer Formationmentioning
confidence: 99%
“…The results indicate that the cavitation effects at lower temperature were more effective than the mechanical effects at higher temperature in the viscosity depression of hydrogel solutions. At higher temperature, clearly the vapor pressure will be higher and so the vapor will enter the cavitation bubble, which leads to the cushioning effect [19,22]. The increased viscosity of the solvent at lower temperatures increases rapid transmission of shock waves and favors the defragmentation of polymer chain at low strain rates [22].…”
Section: Effect Of Temperature On the Rate Of Degradationmentioning
confidence: 99%
“…The effects of various parameters like ultrasound pulse and intensity [12,[17][18][19][20], frequency [20,21], temperature [17,[22][23][24], vapor pressure, volume [19,23,24], solvent [17,22], dissolved gases [21], molecular weight [25,26], and polymer concentration [12,19,20] on the ultrasonic degradation of macromolecules have been studied. The ultrasonic degradation of low density polyethylene at different concentrations, volumes, and temperatures has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PTC and ultrasound techniques in the area of polymerization has been gaining remarkable consideration in industrial and academic arena because it is a potent and versatile technology which offers several advantages. It has been reported that a combination of PTC and ultrasound condition is a valuable technique to enhance the reaction rate in an organic heterogeneous reactions [51][52][53][54][55][56] and also successfully employed in different polymerization techniques to synthesis polymers [57], homopolymers, block copolymers [58], hydrogels [59] and polymer-inorganic composites, etc. [49].…”
Section: Introductionmentioning
confidence: 99%